Mixed Training Program: Helping Seesaw to Develop Blended Learning at the Community Learning Center - Sari, Ruhyat Wulan; Khaerudin, Khaerudin; Kusumawardani, Dwi (Journal of Education Reseach and Evaluation, 2022)
This study aims to produce a mix training program with the help of seesaw to develop blended learning designs, obtain data on feasibility tests and test the effectiveness of the mix training program. The type of research used is research and development with a systems approach that refers to the ADDIE and PEDATI models. Methods of data collection by questionnaires, interviews, observation, study documentation and tests. The data is then analyzed by quantitative data analysis techniques and qualitative data analysis techniques. The results of the study generally indicate that the quality of the prototype training program mix produced based on expert reviews from aspects of learning design, learning materials and media is 80.00%, 93.33%, and 86.66%. Meanwhile, based on the results of one to one and small group trials, the quality of the prototype produced was 85.38%. Based on the results of the expert review and user trials, it can be concluded that the prototype of the designed mixed training program is very feasible to use. Meanwhile, after implementing the seesaw-assisted mix training program to develop blended learning designs at the Community Learning Activity Center, the N-Gain score was 0.62 in the medium category, and the N-Gain score percentage value was 61.70% in the quite effective category. Thus, this mixed training program can improve the performance of the equivalence education tutors of the Community Learning Activity Center to develop blended learning designs.